NDRG1 in Aggressive Breast Cancer Progression and Brain Metastasis. (10th December 2021) - Villodre, Emilly S; Hu, Xiaoding; Eckhardt, Bedrich L; Larson, Richard; Huo, Lei; Yoon, Ester C; Gong, Yun; Song, Juhee; Liu, Shuying; Ueno, Naoto T; Krishnamurthy, Savitri; Pusch, Stefan; et al.
Abstract: Background: N-Myc downstream regulated gene 1 (NDRG1) suppresses metastasis in many human malignancies, including breast cancer, yet has been associated with worse survival in patients with inflammatory breast cancer. The role of NDRG1 in the pathobiology of aggressive breast cancers remains elusive. Methods: To study the role of NDRG1 in tumor growth and brain metastasis in vivo, we transplanted cells into cleared mammary fat pads or injected them in tail veins of SCID/Beige mice (n = 7-10 per group). NDRG1 protein expression in patient breast tumors (n = 216) was assessed by immunohistochemical staining. Kaplan-Meier method with 2-sided log-rank test was used to analyze the associations between NDRG1 and time-to-event outcomes. A multivariable Cox regression model was used to determine independent prognostic factors. All statistical tests were 2-sided. Results: We generated new sublines that exhibited a distinct propensity to metastasize to the brain. NDRG1-high–expressing cells produced more prevalent brain metastases (100% vs 44.4% for NDRG1-low sublines, P = .01, Fisher's exact test), greater tumor burden, and reduced survival in mice. In aggressive breast cancer cell lines, silencing NDRG1 led to reduced migration, invasion, and tumor-initiating cell subpopulations. In xenograft models, depleting NDRG1 inhibited primary tumor growth and brain metastasis. In patient breast tumors, NDRG1 was associated with aggressiveness: NDRG1-high expression was also associated with shorter overall survival (hazard ratio [HR] = 2.27, 95% confidence interval [95% CI] = 1.20 to 4.29, P = .009) and breast cancer–specific survival (HR = 2.19, 95% CI = 1.07 to 4.48, P = .03). Multivariable analysis showed NDRG1 to be an independent predictor of overall survival (HR = 2.17, 95% CI = 1.10 to 4.30, P = .03) and breast cancer–specific survival rates (HR = 2.27, 95% CI = 1.05 to 4.92, P = .04). Conclusions: We demonstrated that NDRG1 drives tumor progression and brain metastasis in aggressive breast cancers and that NDRG1-high expression correlates with worse clinical outcomes, suggesting that NDRG1 may serve as a therapeutic target and prognostic biomarker in aggressive breast cancers.